PRACTISE - PhaRmAcist-led CogniTIve Services in Europe: recruitment and current status - Imfeld-Isenegger, Tamara L. (2017)
Poster presented at the 10th PCNE Working Conference, 1-4 February 2017, Bled, Slovenia